Using frequency regulation to improve the energy efficiency of pumping units in switching circuits with a water tower - Kapanski, A. A. (Vestnik MGTU, 2024)
The development of the water supply system for small settlements involves the use of frequency converters and specialized control algorithms capable of maintaining the pressure level established in the network within certain limits. The implementation of one of the standard schemes involves decommissioning a water tower, which, on the one hand, allows reducing the cost of its maintenance, on the other hand, if the pump fails, the water tower provides a certain supply of water to the consumer, which increases the overall uptime. The paper considers the potential for increasing the energy efficiency of a water supply system when operating well pumps on a water tower through the use of frequency converters. The study has analyzed the operating conditions of more than 300 wells. This has made it possible to establish that most pumps have overestimated pressure values when lifting water into the tower (median excess of about 30 m). For the wells under study, optimization of the operating modes of the pumping units has revealed energy saving potential of up to 50 % by reducing excess pressure and up to 2.0 % due to a reduction in starting power at the moment of engine acceleration. An assessment of the energy saving potential based on similarity theory emphasizes that when the pump motor speed is reduced, it is important to take into account the reduction in its performance, which is a significant limitation in the design of automated control systems. The study results confirm the significant theoretical and practical potential of using frequency converters to improve the efficiency of water supply systems without the need to mothball water towers. The research provides a basis for further developments in the field of optimization and automation of water supply systems in order to achieve high energy efficiency.